New strategies for identifying and masking the bitter taste in traditional herbal medicines: The example of Huanglian Jiedu Decoction - Ke, Xiumei; Ma, Hongyan; Yang, Junxuan; Qiu, Min; Wang, Jianwei; Han, Li; Zhang, Dingkun (Frontiers in Pharmacology, 2022)
Suppressing the bitter taste of traditional Chinese medicine (TCM) largely has been a major clinical challenge due to complex and diverse metabolites and high dispersion of bitter metabolites in liquid preparations. In this work, we developed a novel strategy for recognizing bitter substances, hiding their bitter taste, and elucidated the mechanism of flavor masking in TCM. Huanglian Jie-Du Decoction (HLJDD) with an intense bitter taste was studied as a typical case. UHPLC-MS/MS was used to analyze the chemical components in HLJDD, whereas the bitter substances were identified by pharmacophores. Additionally, the screening results of the pharmacophores were further validated by using experimental assays. The mask formula of HLJDD was effectively screened under the condition of clear bitter substances. Subsequently, computational chemistry, molecular docking, and infrared characterization (IR) techniques were then used to explicate the mechanism of flavor masking. Consequently, neotame, γ-CD, and mPEG2000-PLLA2000 significantly reduced the bitterness of HLJDD. Specifically, mPEG2000-PLLA2000 increased the colloid proportion in the decoction system and minimized the distribution of bitter components in the real solution. Sweetener neotame suppressed the perception of bitter taste and inhibited bitter taste receptor activation to eventually reduce the bitter taste. The γ-CD included in the decoction bound the hydrophobic groups of the bitter metabolites in real solution and “packed” all or part of the bitter metabolites into the “cavity”. We established a novel approach for screening bitter substances in TCM by integrating virtual screening and experimental assays. Based on this strategy, the bitter taste masking of TCM was performed from three different aspects, namely, changing the drug phase state, component distribution, and interfering with bitter taste signal transduction. Collectively, the methods achieved a significant effect on bitter taste suppression and taste masking. Our findings will provide a novel strategy for masking the taste of TCM liquid preparation/decoction, which will in return help in improving the clinical efficacy of TCM.